The Role of Local Government in Empowering Micro, Small and Medium Enterprises in North Luwu Regency - Arsyad L; Edi Indra Setiawan; Arka Damayanti (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This study aims to describe the local government's role and determine the factors driving and inhibiting SMEs' empowerment in the North Luwu Regency. Data collection techniques used are observation, interviews and documentation. The results of the research obtained are that the efforts of the Regional Government in empowering SMEs in North Luwu Regency have been guided by national laws and regulations, namely Law Number 20 of 2008. , facilities and infrastructure, business information, partnerships, business licensing, business opportunities, trade promotions, and institutional support. The government's efforts to strengthen business potential are carried out in several fields: production and processing, marketing, human resources, design and technology. The government's efforts in business protection are to suppress business competition, build the quality of MSMEs both in terms of products through the provision of facilities and infrastructure as well as grant assistance and increase the ability of human resources through entrepreneurship training programs and provide opportunities for MSME actors to enter retail- modern retail in North Luwu Regency. Several factors support the empowerment of SMEs in North Luwu Regency, namely human resources, capital and equipment assistance, natural resource wealth, and government policies. Apart from that, several factors inhibit empowerment in North Luwu Regency, namely budget constraints, human resources, the Covid-19 pandemic and the difficulty of road access to remote locations.